Penggunaan Abu Batu Sebagai Pengganti Sebagian Material Pasir - Budiman; WTP, James (Indonesian Society of Applied Science, 2022)
The concrete industry in Indonesia is very advanced and developing, so the use of construction materials is increasing. Another material is needed as a substitute for fine aggregate for the manufacture of concrete, namely stone ash from the waste stone industry. The purpose of this study was to determine the effect and value of the compressive strength of concrete characteristics with the use of rock ash with mixed variations (10% rock ash, 90% sand), (20% rock ash, 80% sand) and (30% rock ash, 70% sand). with a concrete quality target of Fc' 17.5 Mpa. The method used is the laboratory experimental method referring to the SNI standard. The results showed that the use of stone ash (AB) as a normal concrete mixture affected the compressive strength of concrete. The higher the percentage of stone ash (AB), then the value of the compressive strength of concrete increases. The value of the compressive strength of concrete from rock ash (AB) at the composition of AB 10%, AB 20% and AB 30% was 173.50 kg/cm2, 235.11 kg/cm2 and 239.88 kg/cm2 while normal concrete was 18.59 MPa at the age of 28 days.